2015
DOI: 10.1002/jib.187
|View full text |Cite
|
Sign up to set email alerts
|

Drought-proofing barley (Hordeum vulgare) and its impact on grain quality: A review

Abstract: Barley starch research is currently focused on the biosynthesis (enzymatic pathways), structure and the properties of barley grown under optimal conditions. With only limited information available on the effects of abiotic stress (drought) on starch structure, the need arises to determine the effects of genetic expression, inferring drought tolerance and its impact on starch biosynthesis and structure under terminal drought stress. Using size-exclusion chromatography for the first time can bring an understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 96 publications
1
30
0
Order By: Relevance
“…The result showed that O 2− and H 2 O 2 were both reduced, accompanied with the increasing of ASC level (Figure 2C), which reflects the protective effect of ASC against oxidative damage caused by excess ROS accumulation. Abiotic stress will induce the breakdown of chlorophyll, and therefore chlorophyll content can be used as an indicator of plant damage [24]. We further determined the chlorophyll contents in the infiltrated tobacco leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that O 2− and H 2 O 2 were both reduced, accompanied with the increasing of ASC level (Figure 2C), which reflects the protective effect of ASC against oxidative damage caused by excess ROS accumulation. Abiotic stress will induce the breakdown of chlorophyll, and therefore chlorophyll content can be used as an indicator of plant damage [24]. We further determined the chlorophyll contents in the infiltrated tobacco leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Barley is grown for feed, food or used in industrial applications such as malting (Ullrich 2011, Gous, Gilbert et al 2015. Complex genetic, physiochemical properties, and their associated interactions have resulted in continued attempts to improve barley grain quality (Gous, Gilbert et al 2015). A number of these quality traits directly determine potential end use.…”
Section: Grain Quality and End Usementioning
confidence: 99%
“…Barley (Hordeum vulgare L.) is widely used as food or feed for animals. For malting and brewing purposes specific quality parameters protein content is very important (Gous et al 2015), which is determined by the agronomic practise and by the enviroment. Excessive rates of nitrogen fertilization can increase protein levels.…”
Section: T7: Plant Adaptation and Resilience -Poster Presentationsmentioning
confidence: 99%